The Effects of Employee Involvement Programs on Unionized Workers’ Attitudes, Perceptions, and Preferences in Decision Making - Leana, Carrie R.; Ahlbrandt, Roger S.; Murrell, Audrey J. (Academy of Management Journal, 1992)
This research examined differences in perceptions and attitudes regarding work, the union, and preferences for decision-making structures among three groups: participants and nonparticipants in an employee involvement program, and employees who had volunteered for the program but had not yet had the opportunity to participate. Results indicated that the volunteers generally had the most positive attitudes toward their work and union; participants showed the greatest disparity between their perceived and desired levels of influence. Participants also viewed employee involvement as the best structure for decision making on some work issues; nonparticipants favored collective bargaining.